Characteristics of Saccharomyces cerevisiae yeasts exhibiting rough colonies and pseudohyphal morphology with respect to alcoholic fermentation - Reis,Vanda Renata (2013)
Among the native yeasts found in alcoholic fermentation, rough colonies associated with pseudohyphal morphology belonging to the species Saccharomyces cerevisiae are very common and undesirable during the process. The aim of this work was to perform morphological and physiological characterisations of S. cerevisiae strains that exhibited rough and smooth colonies in an attempt to identify alternatives that could contribute to the management of rough colony yeasts in alcoholic fermentation. Characterisation tests for invasiveness in Agar medium, killer activity, flocculation and fermentative capacity were performed on 22 strains (11 rough and 11 smooth colonies). The effects of acid treatment at different pH values on the growth of two strains ("52" -rough and "PE-02" smooth) as well as batch fermentation tests with cell recycling and acid treatment of the cells were also evaluated. Invasiveness in YPD Agar medium occurred at low frequency; ten of eleven rough yeasts exhibited flocculation; none of the strains showed killer activity; and the rough strains presented lower and slower fermentative capacities compared to the smooth strains in a 48-h cycle in a batch system with sugar cane juice. The growth of the rough strain was severely affected by the acid treatment at pH values of 1.0 and 1.5; however, the growth of the smooth strain was not affected. The fermentative efficiency in mixed fermentation (smooth and rough strains in the same cell mass proportion) did not differ from the efficiency obtained with the smooth strain alone, most likely because the acid treatment was conducted at pH 1.5 in a batch cell-recycle test. A fermentative efficiency as low as 60% was observed with the rough colony alone.